Normal Coronary Artery Patient Presenting with Left Ventricular Aneurysm. (14th June 2011) - Altay, Hakan; Altin, Cihan; Çoner, Ali; Muderrisoglu, Haldun
Abstract : Left ventricular aneurysm (LVA) is one of the most important complications of myocardial infarction LVA is strictly defined as a distinct area of abnormal left ventricular diastolic contour with systolic dyskinesia or paradoxical bulging. LVA usually results from myocardial infarction. Other rare aetiologies of LVA include hypertrophic cardiomyopathy, Chagas' disease, sarcoidosis, congenital LVA, and idiopathic However, LVA formation in patients with idiopathic dilated cardiomyopathy is rarely reported, and the incidence, clinical features, and pathogenesis of LVA formation in patients with idiopathic dilated cardiomyopathy is not well understood. Here, we present a 45 years old, idiopathic dilated cardiomyopathy patient with LVA and normal coronary arteries The pathogenesis of LVA formation in patients with idiopathic dilated cardiomyopathy is not clear. One acceptable hypothesis is that coronary artery emboli originate from mural thrombi, present in some patients with idiopathic dilated cardiomyopathy, which develop due to local wall infarction and fibrosis. The local myocardial perfusion differences could be seen in idiopathic dilated cardiomyopathy and predominantly found in the anteroposterior axis of the left ventricle. Local fibrosis occurs more frequently on the anterior wall or posterior wall, and less frequently on the lateral or septal wall. In our patient, LVA existed in the septal segments.We could not define the exact mechanism of the septal aneurysm in our patient but we decided to present this abnormal case, which is different from cases thus far reported in the literature.